KARAKTERISTIK PENDERITA KONJUNGTIVITIS RAWAT JALAN DI RSUD.DR.PIRNGADI MEDAN TAHUN 2011 - Fivit Y Hutagalung; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Characteristics of patient with outpatient conjungtivitis in RSUD. Dr. Pirngadi Medan 2011. Conjunctivitis is inflammation of the conjunctiva or inflammation was largely a mucous membrane that cover the back of the eyelid and eyeball. Conjunctivitis is one of the ten greatest diesease in RSUD Dr. Pirngadi Medan. Total cases of conjunctivitis and other disorders of conjunctiva 355 visits to the eye departement. To determint the characteristics of patient with conjunctivitis in RSUD Dr.Pirngadi Medan in 2011 with research descriptive case series design. Data were collected from medical records of patient with conjunctivitis in RSUD Dr.Pirngadi Medan in 2011.population were as many as 355 data and sample were as many as 182 data and data obtained by random tables of C.survey program. Data analysis with Chi-Square and Exact-Fisher test. The result showed the highest proportion of patients with conjunctivitis in April of 20,9%, the age group 21-30 years with sex ratio of 1,25, the level of high school education 35,9%, 28,1% student work, where living in Medan 84,1%, the main complaint 100% red eyes, conjunctivitis location decstra-sinistra 52,9%, the type of acute conjungtivitis cataralis 57,1%, non-cobble stones 90,2%, visits an everage of 1 times 71,4% and general cost sources 62,1%. There is statistical test result showed a significant difference in proportion between the ages based on the type of conjunctivitis (p<0,05), conjunctivitis located by type of conjunctivitis (p<0,05), visits an everage by type of conjunctivitis (p<0,05) and visits an everages by cost sources (p<0,0). Expected to people with conjunctivitis in order to increase endurance, hygiene, sanitation and the environment and to the doctors and nurses in RSUD Dr. Pirngadi Medan field in order to provide understanding to patient and their families about the disease conjunctivitis to reduce transmission of the disease to others. Keywords: Conjunctivitis, Characteristics of patiens